Dynamics of male residence and female oestrus during a breeding season of blue monkeys in the Kakamega Forest, Kenya - Mugatha, Simon M.; Ogutu, Joseph O.; Cords, M.; Maitima, J.M. (Wiley, 2007)
Blue monkeys (Cercopithecus mitis stuhlmanni) are seasonal breeders with a dynamic mating system in which typical one-male social units are regularly disrupted and replaced by multi-male ones. The number of males in the group is correlated with the number of oestrous females. We used observations of male presence and female oestrus on individual days during a 6-month period to assess whether the presence of multiple males in a group stimulates female oestrus or whether oestrous females attract multiple males to the group. We confirmed prior observations with our finding that the number of males in a group was significantly correlated (rs = 0.435, P < 0.0001) with the number of oestrous females across 126 observation days. A transition matrix did not show an obvious relationship between day-to-day changes in the numbers of oestrous females and males. However, cross-correlation analysis provided stronger support for the idea that the number of oestrous females attracts males to a group than for the idea that the influx of strange males stimulates oestrus in female blue monkeys. Autocorrelation analysis showed that while female oestrus appeared to show a high degree of synchrony, as expected in a seasonal breeder, there was no evidence that the number of males accompanying a group of females influenced the likelihood of other males joining or leaving the group. Overall, our results confirm that female oestrous behaviour stimulates changes in male residence patterns. However, other observations suggest that changes in male residence may also stimulate female oestrus in some circumstances.